A crystal nucleus-based composite accelerating early strength agent for oil well cement and preparation method thereof
By using crystalline core-based composite coagulation premature strength agent in oil well cement, combined with modified hydrated calcium silicate and amorphous calcium aluminate materials, the problems of poor premature strength and strong hygroscopicity of traditional coagulation agents are solved, and the efficient coagulation and premature strength effects are achieved, while ensuring the durability of cement stone.
Patent Information
- Application Number
- CN202111394577.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-11-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2041-11-23
AI Technical Summary
Traditional oil well cement accelerators have the problem of good coagulation effect and poor premature strength. The compressive strength of cement stones mixed with coagulation agents after long-term curing may be lower than that of cement stones, which affects the durability of cement stones. At the same time, traditional coagulation agents have strong hygroscopic properties, which are prone to deterioration and corrosion of equipment.
The crystal core-based composite coagulation and early strength agent is used, including a mixture of modified hydrated calcium silicate powder and amorphous calcium aluminate powder as crystal core material, combined with organic salts, water reducing agents and organic amines, and through the "crystalline nucleus induction" and "in-situ growth", the activation energy of cement hydration reaction is reduced, the early strength of cement stones is improved, and the hygroscopicity is weakened.
It has achieved efficient acceleration of cement hydration rate, shortened the thickening time of cement slurry, improved the early strength of cement stone, and had no impact on the durability of cement stone, and avoided the problems of hygroscopic deterioration and corrosion equipment.
Smart Images

Figure CN116143440B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of oilfield completion and cementing admixtures, and in particular to a crystal nucleus-based composite accelerating and early-strengthening agent for oil well cement and a preparation method thereof. Background Art
[0002] Oil well cement accelerators are usually used for cementing at low temperatures or surface layers to shorten the thickening time, accelerate cement coagulation and hardening, improve the early strength of cement paste, and meet the requirements of rapid drilling; or to alleviate the over-retardation caused by the addition of other admixtures such as dispersants and fluid loss reducers. Commonly used accelerators generally have the effect of improving the early compressive strength of cement paste in addition to the accelerating effect. However, there are also a few accelerators that have a more obvious accelerating effect but cannot effectively improve the early strength of cement paste. There is no absolute correspondence between accelerating coagulation and early strength.
[0003] At present, the commonly used traditional oil well cement coagulation accelerators / early strength agents are mainly inorganic salts and organic compounds. With the continuous deepening of the research on the hydration mechanism of oil well cement, nanoparticle coagulation accelerators / early strength agents have gradually become a research hotspot in recent years. Inorganic salts are the most commonly used oil well cement coagulation accelerators, among which chlorides have a better coagulation accelerator effect. They also include carbonates, silicates, aluminates, nitrates, sulfates, thiosulfates, and hydroxides of sodium, potassium, and ammonium. Such materials usually have a strong coagulation accelerator effect on oil well cement, but the degree of early strength improvement varies greatly. Some materials also have side effects on the durability of cement stone. In addition, such coagulants are affected by their own properties. Most of them have strong hygroscopicity, especially calcium chloride and aluminum chloride. They will liquefy and deteriorate after being exposed to the air for a short time. Because there are a lot of chloride ions in the coagulants, there will be problems of corrosion of production equipment. Organic compound coagulants / early strength agents mainly refer to organic salts and organic amines. The reaction mechanism of organic compound coagulants is relatively complex, and the regularity of coagulant acceleration and the dosage of the agent are difficult to grasp. Therefore, they are rarely used alone in practical applications, and are often used in combination with corresponding inorganic coagulants. Nanoparticle coagulants / early strength agents are mainly nano-silica, which stimulate the nucleation reaction of cement hydration and accelerate the cement hydration reaction and crystal growth under the action of the crystal nucleus template. However, due to the cost, usage and other issues, most of them are mainly indoor research.
[0004] Application Contents
[0005] The present application provides a crystal nucleus-based composite accelerator for oil well cement and a preparation method thereof, which can solve the problem that traditional accelerators have good accelerating effect but poor early strength effect, and the problem that the compressive strength of cement paste mixed with accelerators may be lower than that of neat cement paste after long-term curing (more than 24 hours), which affects the durability of cement paste, and at the same time, minimize the problem of product deterioration due to moisture absorption.
[0006] This application adopts the following technical solutions:
[0007] The present application provides a crystal nucleus-based composite accelerating and early-strengthening agent for oil well cement, comprising the following components in parts by weight: 40 to 60 parts of crystal nucleus material, 20 to 30 parts of organic salt, 8 to 15 parts of water reducing agent, and 0.5 to 1.0 parts of organic amine.
[0008] Furthermore, the crystal core material includes a mixture of modified hydrated calcium silicate powder and amorphous calcium aluminate powder, wherein the mass ratio of the modified hydrated calcium silicate powder to the amorphous calcium aluminate powder is 3:1.
[0009] Furthermore, the particle size of the modified hydrated calcium silicate powder is 200 to 300 nm.
[0010] Furthermore, the specific surface area of the amorphous calcium aluminate powder is 0.7 to 0.9 m 2 / g.
[0011] Further, the organic salt includes calcium formate and / or sodium formate.
[0012] Furthermore, the water reducing agent comprises a mixture of modified polycarboxylate and sulfonated acetone formaldehyde polycondensate, wherein the mass ratio of the modified polycarboxylate to the sulfonated acetone formaldehyde polycondensate is 1:4.
[0013] Further, the organic amine includes triethanolamine or formamide.
[0014] The present application also provides a method for preparing the above-mentioned crystal nucleus-based composite accelerating and early-strength agent for oil well cement, comprising the following steps: mixing an organic salt with an organic amine to obtain a mixture A. Mixing a crystal nucleus material with a water reducer to obtain a mixture B. Mixing mixture A with mixture B to obtain a crystal nucleus-based composite accelerating and early-strength agent for oil well cement.
[0015] Furthermore, after the organic salt and the organic amine are mixed, they are allowed to stand for 10 to 15 minutes.
[0016] Further, the crystal core material and the water reducing agent are mixed for 5 to 10 minutes using a zero-gravity mixer. The mixture A and the mixture B are mixed for 20 to 30 minutes using a zero-gravity mixer.
[0017] Compared with the prior art, this application has the following beneficial effects:
[0018] The crystal nucleus-based composite accelerating and early strength agent for oil well cement described in the present application, relying on the effects of "crystal nucleus induction" and "in-situ growth", reduces the activation energy of cement hydration reaction, efficiently strengthens the "skeleton" of cementitious materials, cooperates with organic compounds, ionizes a large number of anions and cations to diffuse in the system, effectively accelerates the cement hydration rate, shortens the cement slurry thickening time, improves the early strength of cement paste, has no effect on the durability of cement paste, and has good comprehensive performance. The crystal nucleus-based composite accelerating and early strength agent for oil well cement described in the present application, the selected crystal nucleus and other component materials have weak hygroscopicity, while ensuring the accelerating and early strength effect, it avoids the problems of traditional accelerators hygroscopic deterioration and equipment corrosion. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a schematic flow chart of a method for preparing a crystal nucleus-based composite accelerating and early-strengthening agent for oil well cement of the present application. DETAILED DESCRIPTION
[0020] The technical methods in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0021] The present application provides a crystal nucleus-based composite accelerating and early-strengthening agent for oil well cement, comprising the following components in parts by weight: 40 to 60 parts of crystal nucleus material, 20 to 30 parts of organic salt, 8 to 15 parts of water reducing agent, and 0.5 to 1.0 parts of organic amine.
[0022] The crystal core material is a mixture of modified hydrated calcium silicate powder and amorphous calcium aluminate powder. The mass ratio of the modified hydrated calcium silicate powder to the amorphous calcium aluminate powder is 3:1. The particle size of the modified hydrated calcium silicate powder is 200-300 nm. The specific surface area of the amorphous calcium aluminate powder is 0.7-0.9 m 2 / g.
[0023] The organic salt is calcium formate and / or sodium formate.
[0024] The water reducing agent is a mixture of modified polycarboxylate and sulfonated acetone formaldehyde condensation product, wherein the mass ratio of the modified polycarboxylate to the sulfonated acetone formaldehyde condensation product is 1:4.
[0025] The organic amine is triethanolamine or formamide.
[0026] See also Figure 1 The present application also provides a method for preparing the above-mentioned crystal nucleus-based composite accelerating and early strength agent for oil well cement, comprising the following steps:
[0027] Step 1: Mix an organic salt and an organic amine to obtain a mixture A.
[0028] After the organic salt and the organic amine are mixed, they are left to stand for 10 to 15 minutes. A small mixing tank can be used to mix the organic salt and the organic amine.
[0029] Step 2: Mix the crystal core material and the water reducing agent to obtain a mixture B.
[0030] Wherein, the crystal core material and the water reducing agent are mixed for 5 to 10 minutes using a zero-gravity mixer.
[0031] Step 3: Mix the mixture A and the mixture B to obtain a crystal nucleus-based composite accelerating and early strength agent for oil well cement.
[0032] Wherein, the mixture A and the mixture B are mixed for 20 to 30 minutes using a zero-gravity mixer.
[0033] The crystal nucleus-based composite accelerating and early-strengthening agent for oil well cement of the present application can be used for cementing oil and gas wells with low temperature in shallow land layers, offshore surface layers and special requirements for short-term setting. The accelerating and early-strengthening effects remain consistent, and the strength is continuously improved until the cement stone is completely hardened.
[0034] The technical solutions and beneficial effects of the present application are described in detail below with reference to the embodiments:
[0035] Example 1
[0036] First, 20 parts of a mixture of organic salts - calcium formate and sodium formate, wherein the mass ratio of calcium formate to sodium formate is 5:1, and 0.5 parts of an organic amine - triethanolamine are weighed, with each part being 100 g. Then, the organic salts and organic amines are mixed evenly and allowed to stand for 10 to 15 minutes to obtain a mixture A.
[0037] Then, 60 parts of a mixture of the crystal core material, modified hydrated calcium silicate powder and amorphous calcium aluminate powder were weighed, wherein the mass ratio of the modified hydrated calcium silicate powder and the amorphous calcium aluminate powder was 3:1, the particle size of the modified hydrated calcium silicate powder was 200 nm, and the specific surface area of the amorphous calcium aluminate powder was 0.7 m 2 / g, and weigh 15 parts of a mixture of a water reducer-modified polycarboxylate and sulfonated acetone formaldehyde polycondensate, wherein the mass ratio of the modified polycarboxylate to the sulfonated acetone formaldehyde polycondensate is 1:4. Then, the above-mentioned crystal core material and the water reducer are uniformly mixed to obtain a mixture B.
[0038] Finally, the mixture A and the mixture B are mixed evenly to obtain a crystal nucleus-based composite accelerating and early strength agent for oil well cement, which is recorded as sample #1.
[0039] Example 2
[0040] First, 25 parts of a mixture of organic salt-calcium formate and sodium formate are weighed, wherein the mass ratio of calcium formate to sodium formate is 5:1, and 0.5 parts of organic amine-formamide are weighed, and then the organic salt and the organic amine are mixed evenly and allowed to stand for 10 to 15 minutes to obtain a mixture A.
[0041] Then, 50 parts of a mixture of the crystal core material, modified hydrated calcium silicate powder and amorphous calcium aluminate powder were weighed, wherein the mass ratio of the modified hydrated calcium silicate powder and the amorphous calcium aluminate powder was 3:1, the particle size of the modified hydrated calcium silicate powder was 300 nm, and the specific surface area of the amorphous calcium aluminate powder was 0.9 m 2 / g, and weigh 11 parts of a mixture of a water reducer-modified polycarboxylate and a sulfonated acetone formaldehyde condensate, wherein the mass ratio of the modified polycarboxylate to the sulfonated acetone formaldehyde condensate is 1:4, and mix the above-mentioned crystal core material and the water reducer uniformly to obtain a mixture B.
[0042] Finally, the mixture A and the mixture B are mixed evenly to obtain a crystal nucleus-based composite accelerating and early strength agent for oil well cement, which is recorded as sample #2.
[0043] Embodiment 3:
[0044] First, 30 parts of a mixture of organic salts - calcium formate and sodium formate, wherein the mass ratio of calcium formate to sodium formate is 5:1, and 1.0 part of an organic amine - triethanolamine are weighed, with each part being 100 g. Then, the organic salts and organic amines are mixed evenly and allowed to stand for 10 to 15 minutes to obtain a mixture A.
[0045] Then, 40 parts of a mixture of the crystal core material, modified hydrated calcium silicate and amorphous calcium aluminate were weighed, wherein the mass ratio of the modified hydrated calcium silicate to the amorphous calcium aluminate was 3:1, the particle size of the modified hydrated calcium silicate powder was 250 nm, and the specific surface area of the amorphous calcium aluminate powder was 0.8 m 2 / g, and 8 parts of water reducing agent are weighed, wherein the mass ratio of modified polycarboxylate and sulfonated acetone formaldehyde polycondensate is 1:4. Then, the above-mentioned crystal core material and water reducing agent are uniformly mixed, and recorded as mixture B.
[0046] Finally, the mixture A and the mixture B are mixed evenly to obtain a crystal nucleus-based composite accelerating and early strength agent for oil well cement, which is recorded as sample #3.
[0047] Comparative Example 1:
[0048] According to 100g each, 70 parts of calcium chloride and 30 parts of aluminum chloride were weighed, and the above calcium chloride and aluminum chloride were mixed evenly to obtain a conventional accelerating and early strength agent, which was recorded as 0# comparison sample.
[0049] Test example
[0050] The performance of the samples obtained in the examples of the present application and the comparative samples obtained in the comparative examples were evaluated according to the test methods specified in GB / T 19139-2012 "Test methods for oil well cement" and GB / T 16913-2008 "Test methods for dust properties".
[0051] Test 1: Test the moisture absorption rate (wi) of samples 1#, 2#, 3# and comparison sample 0# under the conditions of temperature 25°C / humidity 50% for 24h, 48h and 5d. The test results are shown in Table 1.
[0052] Table 1. Test results of moisture absorption rate of accelerator under different placement time conditions
[0053]
[0054] Note: ih / d Indicates the moisture absorption rate in the i-th hour / day, m ih / d represents the mass in the i-th hour / day, m m represents the mass of the material after drying, and m1 represents the sum of the mass of the clean container after drying and the mass of the material after drying.
[0055] When the 0# comparison sample was tested at 24h and 48h, it was observed that there were obvious small droplets on the inner wall of the container. After 5d, the moisture absorption rate was as high as 70%, and the material was "semi-liquid, paste-like". However, there was no caking phenomenon in the 1#, 2#, and 3# samples, and there was no obvious change in appearance.
[0056] From the above test results, it can be seen that the conventional accelerating materials represented by the 0# comparative sample have strong hygroscopicity when exposed to the air and are prone to deterioration. However, the crystal nucleus-based composite accelerating early strength agent for powdered oil well cement of the present application represented by samples 1#, 2#, and 3# absorbs moisture slightly, has a large moisture absorption rate within 24 hours, and has little change in quality in the later period. The moisture absorption rate after 5 days is 5-6%, which has basically no effect on the material itself.
[0057] Test 2:
[0058] The cement slurry formula used included:
[0059] Formula 1: G-grade cement + 44% (percentage of cement mass) water, cement slurry density is 1.90g / cm 3 .
[0060] Formula 2: G-grade cement + 45% (percentage of cement mass) water + 2% (percentage of cement mass) accelerator sample, cement slurry density is 1.90g / cm 3 .
[0061] The compressive strength of cement slurry obtained by formula 1 (recorded as blank cement slurry) and cement slurry obtained by formula 2 and using 0# control sample and 1#, 2#, 3# samples (recorded as 0# cement slurry, 1# cement slurry, 2# cement slurry, 3# cement slurry, respectively) with the same addition amount under different temperature conditions and low temperature conditions were tested. The test results are shown in Table 2.
[0062] Table 2. Test results of cement slurry thickening and compressive strength under different temperature conditions
[0063]
[0064] Note: The ratio of thickening time refers to the thickening time of cement slurry mixed with accelerator / thickening time of blank cement slurry.
[0065] From the above experimental results, it can be seen that compared with the blank cement slurry, the thickening time of the 0# cement slurry with the addition of the commonly used accelerator and early strength agent 0# sample is shortened, and the ratio of the thickening time within the test temperature range is greater than 0.49, which has a certain low-temperature early strength effect, but the improvement in 24h strength is limited, and the 7d strength is slightly lower than that of the neat cement paste, which has a negative impact on the durability of the cement paste. The 1#, 2#, and 3# cement slurries with the addition of the 1#, 2#, and 3# samples of the accelerator and early strength agent of this application have significantly shortened thickening time, and the ratio of the thickening time can be kept less than 0.48 within the test temperature range, and the early strength effect is obvious. The 6h strength under low temperature conditions can be greater than 5MPa, and the 24h strength continues to develop. Compared with the neat cement paste, the strength is increased by nearly 30%, and the 7d strength is slightly higher than that of the neat cement paste, which has no effect on the durability of the cement paste.
[0066] Test 3:
[0067] The cement slurry formula used is:
[0068] Formula 3: G-grade cement + 45% (percentage of cement mass) water + x% (percentage of cement mass) accelerator sample, cement slurry density is 1.90g / cm 3 .
[0069] The compressive strength of cement slurries obtained by using formula 3 and samples 1#, 2#, and 3# with different addition amounts under the same temperature conditions and at low temperatures was tested. The test results are shown in Table 3.
[0070] Table 3. Thickening and compressive strength test results of cement slurry under different dosages of accelerators
[0071]
[0072] From the above test results, it can be seen that under the same temperature conditions, the thickening time of cement slurry shortens with the increase of the amount of accelerating and strengthening agent 1#, 2#, and 3# samples, the 6h early strength increases with the increase of the amount of accelerating and strengthening agent, and the 24h compressive strength of cement paste increases with the increase of the amount of accelerating and strengthening agent, with a strong regularity. The compressive strength of cement paste at 7d is basically stable, the compressive strength is slightly improved, and there is no decline.
[0073] The above shows and describes the basic principles, main features and advantages of the present application. Those skilled in the art should understand that the present application is not limited by the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present application. Without departing from the spirit and scope of the present application, the present application may have various changes and improvements, and the scope of protection required by the present application is defined by the attached claims, description and their equivalents.
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A crystal nucleus-based composite accelerating and early-strengthening agent for oil well cement, characterized in that: The composition comprises the following components in parts by weight: 40-60 parts of crystal nucleus material, 20-30 parts of organic salt, 8-15 parts of water reducing agent, 0.5-1.0 parts of organic amine; The crystal core material comprises a mixture of modified hydrated calcium silicate powder and amorphous calcium aluminate powder; The mass ratio of the modified hydrated calcium silicate powder to the amorphous calcium aluminate powder is 3:1; The particle size of the modified hydrated calcium silicate powder is 200-300 nm; The specific surface area of the amorphous calcium aluminate powder is 0.7-0.9 m 2 / g.
2. The crystal nucleus-based composite accelerating and early-strengthening agent for oil well cement according to claim 1, characterized in that: The organic salt includes calcium formate and / or sodium formate.
3. The crystal nucleus-based composite accelerating and early-strength agent for oil well cement according to claim 1, characterized in that: The water reducing agent comprises a mixture of modified polycarboxylate and sulfonated acetone formaldehyde condensation product; The mass ratio of the modified polycarboxylate to the sulfonated acetone formaldehyde polycondensate is 1:
4.
4. The crystal nucleus-based composite accelerating and early-strength agent for oil well cement according to claim 1, characterized in that: The organic amine includes triethanolamine or formamide.
5. A method for preparing the crystal nucleus-based composite accelerating and early strength agent for oil well cement according to any one of claims 1 to 4, characterized in that: The following steps are involved: mixing an organic salt with an organic amine to obtain a mixture A; Mixing the crystal nucleus material and the water reducing agent to obtain a mixture B; The mixture A is mixed with the mixture B to obtain a crystal nucleus-based composite accelerating and early-strengthening agent for oil well cement.
6. The preparation method according to claim 5, characterized in that: After the organic salt and the organic amine are mixed, they are allowed to stand for 10 to 15 minutes.
7. The preparation method according to claim 5, characterized in that: Using a zero-gravity mixer to mix the crystal core material and the water reducing agent for 5 to 10 minutes; The mixture A and the mixture B are mixed for 20 to 30 minutes using the zero-gravity mixer.
Citation Information
Patent Citations
Oil well cement low-temperature composite early-strong coagulation accelerator
CN104774600A
Dispersive chlorine-free low-temperature early-strength agent used for oil well cement and cement mortar including same
CN105347716A